The Concept of Falah al-Darain in Iqbal’s Poetry: A Philosophical and Practical Analysis in the Light of Qur’anic Verses - Wasem Akhter; Dr. Rab Nawaz (Journal of Religion and Society, 2025)
This research investigates the concept of Falah al-Darain success in both worldly and spiritual realms—in the poetry of Allama Iqbal, contextualized through the teachings of the Holy Qur’an. Falah al-Darain encompasses the holistic development of human life, integrating ethical, spiritual, and practical dimensions. The study focuses on Iqbal’s philosophy of Khudi (selfhood) and his emphasis on purposeful action (Tasawwur-e-Amal) as essential pathways toward achieving this dual success. By critically analyzing selected Qur’anic verses alongside Iqbal’s poetic expressions, the research highlights the interconnection of faith (Iman), righteous deeds (Amal-e-Saleh), knowledge (Ilm), and moral conduct in realizing the ideal of comprehensive prosperity. Employing a qualitative and analytical methodology, the study demonstrates that Iqbal’s work not only mirrors Qur’anic guidance but also offers actionable principles for individual and societal development. The findings underscore the continuing relevance of Iqbal’s thought in contemporary Muslim societies, providing insights for intellectual, ethical, and spiritual growth aligned with divine guidance. Keywords: Allama Iqbal , Falah al-Darain, Khudi , Tasawwur-e-Amal ,Faith and Righteous Deeds